Pengaruh Motivasi, Citra Sekolah Dan Persepsi Harga Terhadap Keputusan Santri Dalam Memilih Sekolah Di Dayah Terpadu Al-Muslimun Lhoksukon - M Maimanah; Siti Maimunah; A Adnan; H Heriyana (Jurnal Visioner & Strategis, 2022)
This study examined the effect of motivation, school image, and price perception on students' decisions in choosing a school at the Integrated Dayah Al-Muslimun Lhoksukon. This study used primary data obtained by distributing questionnaires to90 respondents selected using probability sampling method with simple random sampling technique. The data analysis method used was multiple linear regressions with the help of SPSS 16.0. This study showed that motivation significantly influencedstudents' decisions in choosing schools at the Integrated Dayah Al-Muslimun Lhoksukon, school image significantly influenced students' decisions in choosing schools at the Integrated Dayah Al-Muslimun Lhoksukon, and price perceptions significantly influenced students' decisions in choosing schools at the Integrated Dayah Al-Muslimun Lhoksukon. Simultaneously, motivation, school image, and price perception significantly influenced students' decisions in choosing a school at the Integrated Dayah of Al-Muslimun Lhoksukon.